Imagining the other and constructing Israelite identity in the early Second Temple period - Edelman, Diana Vikander; Ben Zvi, Ehud (Library of Hebrew Bible Old Testament studies, 2014)
"This volume sheds light on how particular constructions of the 'Other'contributed to an ongoing process of defining what 'Israel' or an 'Israelite'was or was supposed to be in literature taken to be authoritative in the late Persian and Early Hellenistic periods. It asks, who is an insider and who an outsider? Are boundaries permeable? Are there different ideas expressed within individual books? What about constructions of the (partial) 'Other' from inside, e.g., women, people whose body did not fit social constructions of normalness? It includes chapters dealing with theoretical issues and case studies, and addresses similar issues from the perspective of groups in the late Second Temple period so as to shed light on processes of continuity and discontinuity on these matters. Preliminary forms of five of the contributions were presented in Thessaloniki in 2011 in the research programme, 'Production and Reception of Authoritative Books in the Persian and Hellenistic Period,' at the Annual Meeting of European Association of Biblical Studies (EABS)"--